Inhibition of stress corrosion cracking of AISI 304 stainless steel by molybdate ions at elevated temperatures under salt crust - Cansever, N; Çakir, AF; Ürgen, M (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
In this study, stress corrosion cracking (SCC) occurring under salt crust which develops on the surfaces of hot AISI 304 stainless steels (SS) in neutral solutions was investigated and the inhibition effect of molybdate ions on the SCC of AISI 304 SS under these conditions was examined. Stress corrosion cracking experiments were carried out under static, Wick test and dynamic, slow strain rate test conditions. The static tests were conducted using U-bend specimens in 'chloride' and 'chloride + molybdate' containing solutions. The dynamic tests were carried out using slow strain rate (SSR) testing machine under Wick test conditions in distilled water, 'chloride' and 'chloride + molybdate' containing solutions. In the first group of dynamic tests, the specimens were heated to 100 degrees C and a strain rate of 3.8 x 10(-7) s(-1) was used. In the second group of tests, the specimen temperature was 130 degrees C at a strain rate of 2.76 x 10-7 s(-1) The specimens strained until fracture. The results of both static and dynamic tests indicated that the SCC occured under salt crust in neutral solutions with low chloride ions and cracking could be inhibited by the addition of molybdate ions into the solution. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: SCC; molybdate ions; salt crust; STRAIN-RATE; CHLORIDE SOLUTIONS; ROOM-TEMPERATURE; PITTING CORROSION; NACL SOLUTION; MOLYBDENUM; MEDIA; ACID; SUSCEPTIBILITY; Materials Science; Metallurgy & Metallurgical Engineering